2014
DOI: 10.3389/fonc.2014.00122
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Management of Late Urinary Symptom Flare Following Stereotactic Body Radiation Therapy for Prostate Cancer

Abstract: Purpose: Stereotactic body radiation therapy (SBRT) is increasingly utilized as primary treatment for clinically localized prostate cancer. While acute post-SBRT urinary symptoms are well recognized, the late genitourinary toxicity of SBRT has not been fully described. Here, we characterize the clinical features of late urinary symptom flare and recommend conservative symptom management approaches that may alleviate the associated bother.Methods: Between February 2008 and August 2011, 216 men with clinically l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Recently, Woo et al reported a transient late urinary flare in 13.4% of patients who received ultra-hypofractionated SBRT for localized prostate cancer [11]. This was clinically similar to that described in patients treated with low dose rate (LDR) interstitial brachytherapy [1215] and consisted of an abrupt increase in urinary symptoms following a post treatment nadir, which subsequently returned to previous nadir with conservative management.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Recently, Woo et al reported a transient late urinary flare in 13.4% of patients who received ultra-hypofractionated SBRT for localized prostate cancer [11]. This was clinically similar to that described in patients treated with low dose rate (LDR) interstitial brachytherapy [1215] and consisted of an abrupt increase in urinary symptoms following a post treatment nadir, which subsequently returned to previous nadir with conservative management.…”
Section: Introductionmentioning
confidence: 54%
“…However, a recent Surveillance, Epidemiology, and End Results Program (SEER) based analysis has called into question the safety of these treatments in terms of long term urinary toxicity as compared to conventionally fractionated IMRT [22]. Recently, we reported QOL outcomes for patients treated according to our institutional protocol and noted a small subset of patients who developed a late increase in urinary symptoms following a post treatment nadir that subsequently returned to previous nadir, termed late urinary flare [11]. These patients experienced higher rates of CTCAE-graded dysuria, urinary frequency, urgency, and retention in the first 2 years of follow up after prostate SBRT, and demonstrated significant declines in QOL in the EPIC urinary domain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated an association of delayed radiation-induced cystourethritis and the development of urinary symptoms 1 year after hypofractionated radiotherapy [30], which is consistent with our current finding that hypofractionated radiotherapy results in more severe urinary toxicity compared to conventionally fractionated radiotherapy. The role of inflammation in the pathogenic process of late urinary toxicities is further supported by the observation that these symptoms respond well to oral corticosteroids (dexamethasone 4 mg/day for 1 week followed by 2 mg for 1 week) [16]. Future studies should explore the correlation between target volume dose distribution and late urinary symptoms [31].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is classically described as late urinary flare (LUF), which is defined as a moderate (Grade ≥ 2) late genitourinary toxicity [13,14]. While much of the literature discusses flares in relation to intensity-modulated radiation therapy (IMRT) and brachytherapy treatment modalities [15], LUF has been recently associated with stereotactic body radiation therapy (SBRT) treatment, which manifests as a symptom cluster of dysuria, urinary frequency, urinary urgency, and weak stream occurring anywhere from 6 to18 months after treatment completion [16]. …”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies evaluated here reported at least one instance of late grade 3 or higher urinary toxicity, often requiring instrumentation or transurethral resection of the prostate (TURP). This flare phenomenon has been found to peak between 12 and 18 mo post-treatment, though symptoms resolve by 24 mo in a majority of cases[31]. However, this trend remains a concern and should be further elucidated prior to large-scale adoption of SBRT for low- and intermediate-risk prostate cancer.…”
Section: Discussionmentioning
confidence: 99%